PENGARUH ZAT PENGATUR TUMBUH Benzil Amino Purin (BAP) TERHADAP INDUKSI DAN MULTIPLIKASI TUNAS BROKOLI Brassica oleraceae L. var. italica Plenck - Elvis Sagai; Beatrix Doodoh; Deanne Kojoh (COCOS, 2016)
ABSTRACTThis study aims to find out about the effect of plant growth regulators BAP on induction and multiplication shoots of broccoli Brassica oleracae L. var. italica Plenck. This study has been carried out at the Laboratory of Biotechnology Faculty of Agriculture for 3 months starting from April to July 2016. This study used a completely randomized design (CRD), which consists of a single factor, namely the concentration of BAP with 6 treatments and 4 replications. Shoots of broccoli isolated from sterile sprouts and maintained on shoots induction medium consisting of Murashige and Skoog basic medium. Benzylaminopurine (BAP) with a concentration of 1 ppm to 5 ppm is added to the media for inducing and multiplication shoots of broccoli. Results of the study showed that with a concentration of 1 ppm BAP,2 ppm and 5 ppm induce shoots faster than other treatments while the number of buds Award BAP concentration of 1 ppm, 4 ppm and 5 ppm produced the highest number of shoots among other treatments.Keywords: Shoots of broccoli, Benzilaminopurin, induction and multiplication